Australia-wide Point Prevalence Survey of Antimicrobial Prescribing in Neonatal Units: How Much and How Good?. Issue 8 (August 2015) - Osowicki, Joshua; Gwee, Amanda; Noronha, Jesuina; Britton, Philip N.; Isaacs, David; Lai, Tony B.; Nourse, Clare; Avent, Minyon; Moriarty, Paul; Francis, Joshua R.; Blyth, Christopher C.; Cooper, Celia M.; et al.
Abstract : Background: There is increasing recognition of the threat to neonatal patients from antibiotic resistance. There are limited data on antimicrobial prescribing practices for hospitalized neonates. We aimed to describe antimicrobial use in hospitalized Australian neonatal patients, and to determine its appropriateness. Methods: Multicentre single-day hospital-wide point prevalence survey in 2012, in conjunction with the Antimicrobial Resistance and Prescribing in European Children study. The appropriateness of antimicrobial prescriptions was also assessed. All patients admitted at 8 am on the survey day, in 6 neonatal units in tertiary children's hospitals across 5 states, were included in an analysis of the quantity and quality of all antimicrobial prescriptions. Results: The point prevalence survey included 6 neonatal units and 236 patients. Of 109 patients (46%) receiving at least 1 antimicrobial, 66 (61%) were being treated for infection, with sepsis the most common indication. There were 216 antimicrobial prescriptions, 134 (62%) for treatment of infection and 82 (38%) for prophylaxis, mostly oral nystatin. Only 15 prescriptions were for targeted as opposed to empirical treatment. Penicillin and gentamicin were the most commonly prescribed antibiotics, with vancomycin third most common. Half of all treated patients were receiving combination antimicrobial therapy. There was marked variation in vancomycin and gentamicin dosing. Overall, few prescriptions (4%) were deemed inappropriate. Conclusion: This is the first Australia-wide point prevalence survey of neonatal antimicrobial prescribing in tertiary children's hospitals. The findings highlight positive practices and potential targets for quality improvement. Abstract : Supplemental Digital Content is available in the text.